Faeces - Urine separation via settling and displacement: Prototype tests for a novel non-sewered sanitation system - Hennigs, Jan; Ravndal, Kristin T.; Parker, Alison; Collins, Matt; Jiang, Ying; Kolios, Athanasios J.; McAdam, Ewan; Williams, Leon; Tyrrel, Sean F. (Elsevier, 2020)
The development of novel, non-sewered sanitation systems like the Nano Membrane Toilet requires thorough investigation of processes that may seem well-understood. For example, unlike the settling of primary sludge, the separation of solids from liquids in a small-volume container at the scale of a household toilet has not been studied before. In two sets of experiments, the settling of real faeces and toilet paper in settling columns and the settling of synthetic faeces in a conical tank are investigated to understand the factors affecting the liquid quality for downstream treatment processes. Toilet paper is found to be a major inhibitor to settling of solids. While a lower overflow point results in better phase separation through displacement of liquid, a higher overflow point and frequent removal of solids may be more advantageous for the liquid quality
Keywords: DOE; Prototyping; Testing